Rancang Bangun Aplikasi Penentuan Promosi Perawat Mahir Pada RUmah Sakit PHC Surabaya - Sanjaya, Shigit Hussein; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract: Primasatya Husada Citra (PHC) Hospital Surabaya is a sub company of PT. Pelabuhan Indonesia III. Problem in PHC Hospital Surabaya is when selection 1 phase (administration) on process. Viewed nurse data search process is still manual, there is 25% more or less nurses in special unit that not yet work for 3 years. The effect is the nurses performance do not give a maximum result because there is not enough work experience. Beside of that, less precise selection of experienced nurses who are promoted because only look from 2 criteria. The other problems there are3 more or less record of nurses peer review scoring is gone. The solution that offered to helping all of the problem is an determination promotion of experienced nurses application with graphic rating scales method which can process the data from the criteria that needed so that obtain list of the candidate and candidate information’s that suitable by hospital need. The result of the research showed the application that have already made are can helping in the process of calculating the promotion and generate nurse’s report and nurse overall report.Keywords: application, promotion determination, graphic rating scales.